Challenges and Opportunities for Purchasing High-Quality Health Care : Lessons from Armenia - Chukwuma, Adanna; Lylozian, Hratchia; Gong, Estelle (Taylor and Francis, 2021)
This paper examines how purchasing decisions in Armenia may contribute to barriers in using high-quality health care, particularly for non-communicable diseases, drawing on a review of the literature and key informant interviews. The paper adapts the strategic health purchasing progress framework, to examine how characteristics of purchasing, the health system, and the political, administrative, and macro-fiscal environment may have facilitated or hindered the attainment of service delivery goals. We conclude with six lessons for reforms aimed at improving the coverage and quality of health care in Armenia. First, increasing the political priority of access to quality of health care is a pre-requisite to advancing reforms to address these issues. Second, improved purchasing governance in Armenia will require a purchaser that can make decisions without political interference, with appropriate accountability mechanisms, improvements in technical capacity, and the routine use of data systems. Third, there is a need for the regulatory framework to ensure that revisions of the benefits package contribute to reducing the disease burden and improving access to care. Fourth, regulations governing quality-related criteria for provider selection should be enforced and include considerations for process quality. Fifth, payment incentives should be revised to encourage an increase in the supply of primary health care, reduce bypassing for hospital care, and improve the quality of services. Sixth, the potential of purchasing to improve service delivery will be dependent on increased pre-paid and pooled funds and better governance of the quality of care.